Effect of chromium toxicity on growth, chlorophyll and some macronutrients of Solanum lycopersicum and Solanum melongena - GAUTAM, MAMTA; SINGH, ANIL KUMAR; JOHRI, RAJIV MOHAN (The Indian Journal of Agricultural Sciences, 2014)
A study was conducted to evaluate the effect of Cr on growth, photosynthetic pigment and nutrient uptake of tomato (Solanum lycopersicum L.) and eggplant (S. melongena L.). Tomato and eggplant crops were irrigated with waters having four concentrations of Cr (0.1, 0.5, 2.5 and 7.5 ppm). Normal water was used as control (0 ppm) in both the crops. Application of Cr contaminated irrigation water decreased plant height, leaf area/plant, number of fruits/ plant, fresh fruit weight/plant, fruit yield/plant, dry weight/plant, above plant biomass/plant. The decrease summarized for various parameters across treatments ranged from 62% to 84% and 56% to 77% in tomato and eggplant, respectively. The inhibitory effects on photosynthetic pigments gradually increased with increase in concentration. 7.5 Cr ppm concentration resulted in the lowest pigment level (mg/g FW) and maximum inhibition rate compared to control. It was also observed that the N, P and K content in fruits were significantly affected by the Cr treatments in both the crops. Accumulation of Cr was more in tomato compared to eggplant indicating that tomato was more sensitive to chromium when compared to eggplant. The impact of Cr on the various parameters quantified by using linear, exponential, quadratic and polynomial of degree 3. The responses were described by the polynomial of degree 3 with R2 > 99% for the both crops.